FAKTOR-FAKTOR YANG MENENTUKAN KEBIMBANGAN KARIER PADA SISWA SMA KELAS XII - Akmal, Sari Zakiah (Faculty of Psychology, Diponegoro University, 2019)
Career decision is one of the major issue among XII grade of high school students, particularly choosing major in university. Most of high school students experience career indecision. There are some factors that predict career indecision problems among adolescents. This study aims to identify factors that significantly affect career indecision among high school students, particularly personality and career decision making self-efficacy factors. This study used quantitative method and data were collected using Indonesian version of Big Five Inventory, Career Decision Making Self-Efficacy Scale, and Career Decision Scale. We recruited 259 participants using incidental sampling (65.3% female, M age = 16.67 years, SD = .62). Hierarchical regression analysis demonstrated that personality factors, particularly openness to experiences and neuroticism predicted career indecision among high school students. Neuroticism was associated positively and openness to experiences was correlated negatively with career indecision. Meanwhile, career decision making self-efficacy was not correlated with career indecision. Therefore, practitioner should design an intervention to overcome student’s career indecision problem by reducing anxiety, decreasing fear in career decision making and encouraging students to looking for more information about their interest and career path.